Incidence of New Onset Atrial Fibrillation in Patients with Acute Coronary Syndrome (ACS) - Ali, Noor; Khan, Abdul Ghaffar; Shah, Rahat; Ali, Abdul; Arshad, Alexander; Ali, Arwan (Indus Journal of Bioscience Research, 2025)
Background: Atrial fibrillation (AF) is one of the most common arrhythmias associated with acute coronary syndrome (ACS). Whether newly developed AF in the context of ACS is deleterious to hemodynamic stability, increases the risk of complications, or raises the chance of fatality remains uncertain. Identifying the incidence of AF, as well as the relevant risk factors, is essential to enhancing prompt management and clinical outcomes. Objectives: Establishing the incidence of new-onset atrial fibrillation in patients with acute coronary syndrome while assessing the relationships of associated clinical-demographic variables and in-hospital outcomes. Study Design: A cross-sectional study. Place and duration of study. Cardiology Department Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta, from December 2024 to May 2025. Methods: In the cardiology department a cross-sectional study involving 120 patients admitted with a primary diagnosis of acute coronary syndrome was undertaken. Individual demographic and clinical details were systematically recorded. During the hospitalization, the patients' electrocardiograms were monitored to identify possible new-onset atrial fibrillation. The analysis was conducted with the SPSS software, version 24.0. For the study variables, averages and standard deviations were determined, and the relationships between variables were tested using chi-square, and t-test procedures with an alpha of 0.05. Results: The 120 patients with Anterior Cardiac Syndrome had an age average of 59.3 ± 10.8 years. There were 70 (58.3%) men and 50 (41.7%) women. During their hospital stay, 11 patients (9.2%) present with new onsets of AF. The patients suffering from AF had a statistically significant Lower left ventricle ejection fraction (42.1 ± 7.9%) as compared to patients without AF (50.6 ± 8.3%, p = 0.004). Older age and increased serum creatinine levels were also statistically significant (p = 0.032 and p = 0.018). Conclusion: About 9% of patients with acute coronary syndrome develop new-onset atrial fibrillation which relates significantly to advanced age, kidney disease, and lower left ventricular ejection fractions. The complications of atrial fibrillation in the setting of acute coronary syndrome require aggressive recognition and management to reduce the risk of thrombosis and improve the short- and long-term outcomes of the patients.